2017
DOI: 10.1140/epjst/e2016-60317-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grafting on the binding transition of two flexible polymers

Abstract: We investigate the binding transition of two flexible polymers grafted to a steric surface with closeby end points. While free polymers show a discontinuous transition, grafting to a steric flat surface leads to a continuous binding transition. This is supported by results from Metropolis and parallel multicanonical simulations. A combination of canonical and microcanonical analyses reveals that the change in transition order can be understood in terms of the reduced translational entropy of the unbound high-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This remains valid upon grafting the polymer onto a steric surface (i.e., restricting the polymer conformations to the upper half-space, z ≥ 0), as shown in Figure , where we present the full structural phase diagram for the grafted polymer of length N = 40. As for flexible polymers, , the structural behavior differs only marginally between the grafted and free polymer; that is, in both cases we observe the same typical conformations. The main difference is the reduction in rotation over the half-sphere about the fixed tail end of a grafted polymer compared to the rotation over the full sphere about the center-of-mass of a free polymer (apart from the obvious translational degrees of freedom).…”
Section: Resultssupporting
confidence: 56%
“…This remains valid upon grafting the polymer onto a steric surface (i.e., restricting the polymer conformations to the upper half-space, z ≥ 0), as shown in Figure , where we present the full structural phase diagram for the grafted polymer of length N = 40. As for flexible polymers, , the structural behavior differs only marginally between the grafted and free polymer; that is, in both cases we observe the same typical conformations. The main difference is the reduction in rotation over the half-sphere about the fixed tail end of a grafted polymer compared to the rotation over the full sphere about the center-of-mass of a free polymer (apart from the obvious translational degrees of freedom).…”
Section: Resultssupporting
confidence: 56%
“…Lastly, we also investigated the binding transition of two flexible polymers grafted to a steric surface with close-by grafting points. 26 While free polymers show a discontinuous binding transition, grafting to a steric flat surface leads to a continuous transition. A combination of canonical and microcanonical analyses revealed that the change in transition order can be understood in terms of the reduced translational entropy of the unbound high-temperature phase upon grafting.…”
Section: Grafted Bundles Of Semiflexible Polymersmentioning
confidence: 99%
“…25 The effect of grafting on aggregation has been investigated by employing similar models as above, demonstrating how it altered the aggregation transition between two polymers from discontinuous to continuous without significantly affecting structural properties. 26 Besides grafting, the aforementioned experimental methods often require external forces on probed polymers, whose effect on emerging struc-tures and the phase space in total is yet to gauge. Modeling single polymers as self-avoiding random walks on a regular lattice under external force has shown how a strand unravels under increased tension.…”
Section: Introductionmentioning
confidence: 99%
“…Note that while in many scalar implementations of multicanonical simulations no thermalization steps are used between iterations, for the large number of parallel walkers employed here and the resulting small number of updates per iteration and walker we find the equilibration steps to be crucial for achieving a stable parallel procedure. Recent applications of the parallel multicanonical method (on CPU clusters) include studies of the Blume-Capel spin model in 2D [28] and 3D [20], lattice and off-lattice particle condensation [29][30][31][32], continuum formulations of the aggregation process of flexible [32,33] as well as semiflexible [34] polymers, the binding transition of grafted flexible polymers [35], the phase diagram of semiflexible polymers [36], and the interplay of semiflexibility with the adsorption propensity of polymers [37]. In all these different cases, the method proved to be very robust and reliable to use routinely in day-by-day practical work.…”
Section: Parallel Multicanonical Samplingmentioning
confidence: 99%